Divergence of Views in Terms of the Concept Anger: Universality and Culture Specifitty - Ubaydullayeva Dilafruz Fazliddinovna (Zien Journals, 2023)
In this study I'll point out that the English word ‘anger’ and its synonymous constituents in Uzbek and English languages are maintained on generalities of anger that have to deal with a lot of complexity. This abstract complexity comes out from several coffers (1) the conceits and metonymies that apply to the concepts in various languages (2) the prototypes of anger that people partake in these societies, and (3) the numerous different senses that the word anger and its counterparts have in different languages. We can ask Are there any universal aspects of the conception(s) of anger?
Keywords: Different languages